The Effect of Small Sided Games and Zig-Zag Run Training on Improving the Dribbling Ability of Samba JR Soccer Players - Marda, Febri; Lanos, Muhsana El Cintami; Rosani, Meilia (PPSDP International Journal of Education, 2024)
There is needed training that can improve dribbling skills in soccer games. Small sided games and zig-zag run exercises are training models that can help players hone their dribbling skills on the field that is small from the real field and plus zig-zag run training through obstacles so that players can practice well. This study uses true-experimental methods also needs to have two types of groups, namely the treated group and the untreated group (control group). In this experimental study there were two groups that had different treatments. The result showed that participants who underwent small sided games showed a greater improvement in dribbling ability compared to those who underwent zig-zag run training. This study contributes that both small sided games and zig-zag run training can have a positive impact on improving dribbling ability in soccer players.